A Note on Literature Review Related to “Oral Azithromycin Versus Oral Doxycycline in the Treatment of Meibomian Gland Dysfunction: A Systematic Review and Meta-Analysis” [Letter] - Safir M; Mimouni M; Ben Ephraim Noyman D (Clinical Ophthalmology)
Margarita Safir,1,2 Michael Mimouni,3,4 Dror Ben Ephraim Noyman3,4 1Ophthalmology Department, Rabin Medical Center, Petah Tikva, Israel; 2Sackler School of Medicine, Tel Aviv University, Tel Aviv, Israel; 3Ophthalmology Department, Rambam Health Care Campus, Haifa, Israel; 4Ruth and Bruce Rappaport Faculty of Medicine, Technion - Israel Institute of Technology, Haifa, IsraelCorrespondence: Dror Ben Ephraim Noyman, Email dror.ben.ephraim@gmail.com